From static snapshots to dynamic panoramas: the evolution and future vision of palliative care atlas in cross-national perspectives - Vilma A. Tripodoro; Juan José Pons; Fernanda Bastos; Eduardo Garralda; Álvaro Montero; Ana Cristina Béjar; Carlos Centeno (Springer, 2024)
Abstract Palliative care is essential to global health services as it improves the quality of life of patients, their families and caregivers. The ATLANTES Global Observatory of Palliative Care (University of Navarra) was created a decade ago to promote a positive attitude towards patients with advanced illness in society and medicine. To do so, and over the past 15 years, ATLANTES has mapped palliative care data worldwide using public health, macro and comparative perspectives in different atlases. These have enabled data to be contextualised and good examples to be identified concisely and graphically. Atlases have been widely employed as advocacy tools within international institutions and ministries of health. While the aim and the perspective have remained unalterable over time, the methods and design have evolved throughout the publications from sober cartography and static infographics to big interactive data visualisation web tools. By embracing technology, ATLANTES has developed an open-access web mapping tool reuniting information from regional atlases, favouring global access to data. In 2022, matching the increasingly recognised need for robust monitoring of palliative care worldwide, ATLANTES became a WHO Collaborating Centre for the Global Monitoring of Palliative Care Development. This attempt to bridge the gap and ensure equitable care information in countries with limited palliative care access has resulted today in more accessible, self-explanatory, and visually appealing palliative care data.